2003
DOI: 10.1177/0734242x0302100105
|View full text |Cite
|
Sign up to set email alerts
|

Plasma chemical gasification of sewage sludge

Abstract: The possibility for plasma gasification of sewage sludge is investigated. Water steam is used as the plasma generating gas and as a chemical reagent. The experiments are carried out at a sludge to water steam ratio of 1 to 1.5 by weight, and at a plasma torch temperature of up to 2600 degrees C. The calculated average temperature in the reactor after mixing with the sludge particles is up to 1700 degrees C. Proximate and ultimate analyses of the sludge are given. The resulting gases are analysed by gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Technically, this performance reduces the gasification times and enhances the quality of the syngas, since less oxidant compounds are required to complete reactions and, consequently, a richer gas in terms of hydrogen (H 2 ) is obtained. For example, Balgaranova (2003) demonstrated that a mixture of 94%vol of H 2 and CO syngas from sludge PTG can be obtained containing less than 4%wt of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Technically, this performance reduces the gasification times and enhances the quality of the syngas, since less oxidant compounds are required to complete reactions and, consequently, a richer gas in terms of hydrogen (H 2 ) is obtained. For example, Balgaranova (2003) demonstrated that a mixture of 94%vol of H 2 and CO syngas from sludge PTG can be obtained containing less than 4%wt of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Another problem appears when the waste contains in its composition heavy metals; using well known incineration for their utilization leads to formation of ash, which is itself a hazardous waste [19][20][21]. The latter environmental hazard is particularly dangerous in the case of recycling the sewage sludge of urban wastewater treatment plants [13].…”
Section: Waste-to-energy Processmentioning
confidence: 99%
“…Sewage sludge has also been studied as potential source of energy [21][22][23][24][25][26], and as raw material for conventional [27,28] and nonconventional products [29,30]. In addition to these applications, sewage sludge can be also used as source of information to seek potential anomalous levels of exposure of a population to POPs: indeed, the dominant exposure route of POPs released by the most important sources (e.g.…”
Section: Journal Of Bior Emediation and Biodegradationmentioning
confidence: 99%